1992
DOI: 10.3109/00952999209051042
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Norms and Expectations as Predictors of Alcohol Use and Problems in a College Student Sample

Abstract: Two-hundred thirty-one alcohol-using college students completed a questionnaire on their levels of alcohol use, moderate to severe problems with alcohol use, expectations of the effects of alcohol on their own and others' moods and behaviors, the desirability of these effects, norms of significant others for levels of alcohol use and the subject's desire to comply with these norms, reasons for drinking and not drinking alcohol, and a personality measure. Expectations of alcohol effects, norms of significant ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
127
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 20 publications
10
127
1
Order By: Relevance
“…However, this finding is not consistent across studies. Wood, Nagoshi, and Dennis (1992) found that impulsivity was related to higher rates of alcohol consumption but not alcohol-related problems after accounting for alcohol consumption.…”
Section: Predictors Of Alcohol-related Consequencesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this finding is not consistent across studies. Wood, Nagoshi, and Dennis (1992) found that impulsivity was related to higher rates of alcohol consumption but not alcohol-related problems after accounting for alcohol consumption.…”
Section: Predictors Of Alcohol-related Consequencesmentioning
confidence: 96%
“…However, this finding is not consistent across studies. Wood, Nagoshi, and Dennis (1992) found that impulsivity was related to higher rates of alcohol consumption but not alcohol-related problems after accounting for alcohol consumption.Others, however, have demonstrated that impulsivity and use are jointly predictive of alcohol-(Simons, 2003) and marijuana-related problems (Simons & Carey, 2002).Drinking motives-It has been suggested that motivation for drinking can have an effect on drinking outcomes. Wood et al (1992) found that negative alcohol outcome expectancies (e.g., impairment, hostility) and pathological reasons for drinking (e.g., drinking when nervous, angry, or sad) were related to higher levels of alcohol-related problems.…”
mentioning
confidence: 96%
“…The literature in Table 3 reveals that perceived normative support of others for drinking consistently predicts personal alcohol use (Clapp & McDonnell, 2000;Liccione, 1980;Lo, 1995;Nagoshi, 1999;Nagoshi, Wood, Cote, & Abbit, 1994;Perkins & Wechsler, 1996;Turrisi, 1999;Werner, Walker, & Greene, 1996;Wood, Nagoshi, & Dennis, 1992;Wood et al, 2001), and, to a lesser extent, alcohol-related problems (Nagoshi, 1999;Wood et al, 1992Wood et al, , 2001. Therefore, the more the student perceives others as drinking heavily, or approving of heavy use, the higher personal consumption will be.…”
Section: Norms and Drinking Behaviormentioning
confidence: 99%
“…Outcomes often assumed to be negative, such as irresponsibility or increased motor impairment, are sometimes evaluated as positive incentive motivators (Fromme et al 1994). With respect to the differentiator model, alcohol abusers cite both euphoria and reducing negative affect as motivation to drink (Wood et al 1992). Drinkers who hope to reduce tension may find sedative effects more desirable and thereby evaluate effects on the descending limb more positively.…”
mentioning
confidence: 99%